2018
DOI: 10.1097/brs.0000000000002743
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-based Approach to the Management of Children With Morquio A Syndrome Presenting With Craniocervical Pathology

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…36,43 Additionally, five articles specific for MPS-IV concluded that radiological evidence of atlantoaxial instability or spinal cord compression warrants surgical intervention, even in the absence of symptoms. 36,41,42,47,50 Contrastingly, prophylactic surgery for MPS-VI was not recommended in any study, and three studies specific for MPS-VI stated that cervical myelopathy must be present for surgery to be indicated. 18,49,51 Surgical management of cranio-cervical pathology Twenty-three articles discussed the surgical management of craniocervical pathology in MPS, involving 232 patients with a median follow-up of 7.6 years (range 2 days-21.4 years).…”
Section: Cranio-cervical Pathologymentioning
confidence: 95%
See 2 more Smart Citations
“…36,43 Additionally, five articles specific for MPS-IV concluded that radiological evidence of atlantoaxial instability or spinal cord compression warrants surgical intervention, even in the absence of symptoms. 36,41,42,47,50 Contrastingly, prophylactic surgery for MPS-VI was not recommended in any study, and three studies specific for MPS-VI stated that cervical myelopathy must be present for surgery to be indicated. 18,49,51 Surgical management of cranio-cervical pathology Twenty-three articles discussed the surgical management of craniocervical pathology in MPS, involving 232 patients with a median follow-up of 7.6 years (range 2 days-21.4 years).…”
Section: Cranio-cervical Pathologymentioning
confidence: 95%
“…Evidence of cervical myelopathy or progressive neurological compromise was unanimously accepted as a surgical indication. 8,18,25,31,34,36,37,[41][42][43][44][46][47][48][49]51 Cervical spinal cord signal change on MRI was considered an indication for surgery in six studies, 31,36,41,42,44,47 while pathological reflexes on neurological examination were reported as an indication in two studies. 41,44 The indications for cervical surgery were notably less stringent for MPS-IV than for other MPS subtypes, with two studies advocating for prophylactic occipitocervical fusion prior to the development of any clinical or radiological abnormailities.…”
Section: Cranio-cervical Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…), inborn errors of metabolism (mucopolysaccaridosis, including Hunter syndrome, Morquio syndrome, Shy syndrome, etc. ), traumas and tumours (26)(27)(28)(29).…”
Section: Advancedmentioning
confidence: 99%
“…The incidence of MPS IV ranges from 1/76,000 births in Northern Ireland to 1/640,000 births in Australia, with some symptoms presenting as late as 3 years of age [1,4]. Most previous orthopedic studies on MPS IV have focused on the atlantoaxial stability of the cervical spine [2,[7][8][9][10]; however, fewer studies have investigated the severity of lower extremity deformities including genu valgum, ankle valgus, progressive hip dysplasia, and other physical attributes, such as joint laxity, and their impact on 3D gait patterns [7,8]. Thus, further investigations to understand the variability in lower extremity deformities in children with MPS IV and the relationship between their severity and dynamic outcomes are warranted.…”
Section: Introductionmentioning
confidence: 99%